Studi Komparatif: Karakteristik Korban Bullying Pada Laki -Laki dan Perempuan - Khoirunnisa, Cahyani; Jamilah, Vera; Nissa, Melanie Syarifatun; Silvia, Nida; Wahyu, Ahmad (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the characteristics of bullying victims among males and females and the resulting psychological, social, and academic impacts. A qualitative method was employed through face-to-face interviews with four adolescents, comprising two males and two females who experienced bullying. The findings revealed that male victims tend to experience physical bullying related to physical weaknesses or appearance, while female victims are more often subjected to verbal and social bullying. Psychological impacts include decreased self-esteem, anxiety, and depression, with deeper effects observed in females. Social impacts, such as withdrawal from social interactions, were evident in all respondents, while academic impacts were more prominent in females reporting decreased performance due to a lack of safety in school. This study also highlights the importance of social support and professional assistance as crucial strategies to mitigate the negative effects of bullying. The study's limitations include a small sample size and a focus on individuals without considering group dynamics or institutional policies. Future research is recommended to explore effective interventions for preventing bullying and supporting victim recovery.